Do governments develop humans? The relationship between government quality and human development - Jovanovic,Marko (2023)
The understanding of development is changing over time. It came a long way from a simple vision of economic progress to the contemporary human-centred perspective. However, the majority of research on institutional impacts continues to focus exclusively on the economic sphere. Thus, I decided to adopt this theoretical concept in a modern, human-oriented framework and analyse how government quality affects human development. In order to do this, I am estimating an OLS panel as it will give straightforward results that can serve as a foundation for further research. I analysed the relationship between government quality and human development on global and regional levels in a sample of 162 countries for the period between 2010 to 2019. The results varied dramatically across regions, thus, suggesting that higher government quality is not necessarily associated with human development. That said, further research is needed to understand the long-term and indirect relationship between government quality and human development.
Keywords: human development; government quality; institutions